PERAN NOTARIS DALAM PERLINDUNGAN HUKUM TERHADAP PIHAK KETIGA ATAS PEMBUATAN PERJANJIAN PERKAWINAN SETELAH PERKAWINAN BERLANGSUNG - Septian Putri Nindiasari; Dominikus Rato; Moh. Ali (Universitas Islam Darul Ulum, 2022)
One of the legal consequence of a marriage is a consolidation of husband and wife assets with the understanding that both parties before signing the marriage contract can decide otherwise, through the pre-nuptial contract. The Constitutional Court Decision No. 69/PUU-XII/2015, made possible the making of a similar arrangement after the marriage contract has been signed. The focus of this article is to explore, using a juridical normative approach, what legal protection exist for third parties. The main finding is that legal protection is provided by requiring the contract be made by and before a notary public, registered at the Civil Registrar Office and all that is performed only after the Notary Public made an inventory of both spouse’s assets.